Analisis Konsep Fisika pada Permainan Tradisional Kerapan Kereweng sebagai Bahan Ajar Fisika - Dina Afkarina; Sudarti . (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2021)
Indonesia is a country rich in local wisdom and spread throughout the region. But along with the times, local wisdom is fading, so that it’s necessary to preserve local wisdom. In education, the preservation of local wisdom can be done by integrating traditional games into learning. The purpose of this study was to analyze the concept of physics in kerapan kereweng traditional game as a physics teaching material. The research method used is a qualitative descriptive research method with an ethnophysical approach. Data was collected by observation, interviews, and documentation. This research illustrates that the kerapan kereweng traditional game is related to the concept of physics, especially the concept of force and motion. The existence of this research is expected to explain the concept of physics in kerapan kereweng traditional game so that it can be used as physics teaching material.